Comparing the morphologies and adsorption behavior of electrospun polystyrene composite fibers with 0D fullerenes, 1D multiwalled carbon nanotubes and 2D graphene oxides - Natalia Hoogesteijn von Reitzenstein (Elsevier, 2022)
Nanoscale adsorbents with unique engineered morphologies give them properties that can be transformative for water treatment. Unlike bulk-scale and top-down sorbents such as activated carbon, bottom-up nanoscale adsorbents dispersed into water are difficult to recover from water unless enmeshed in macro-scale architectures. Electrospinning is a facile and scalable method of immobilizing nanomaterials (NM) including fullerenes (C60), multi-walled carbon nanotubes (MWCNT) and graphene oxide (GO) into non-woven, flexible polymeric fabric architectures. In this study, electrospinning was used to compare three types of NM-polystyrene (PS) composites. The integration of NMs into electrospun fibers created pores, increased fiber diameter, decreased polymer beading and maintained fibers’ surface pore size distribution for all composites. The scanning electron microscopy inspection indicated that GO in electrospun PS coated the surface of the fibers. This was attributed to the 2D sheet like structure of GO that was pushed outside by the evaporating organic solvent during electrospinning. Phenanthrene adsorption experiments indicated that GO preserved adsorptive properties when incorporated into PS whereas MWCNT and C60 did not. The restricted adsorption of MWCNT and C60 was caused by the concealing of NMs within the PS filaments. On the other hand, partial exposure of GO surfaces enabled adsorption of phenanthrene by GO. Despite the similarities in pore formation and increased diameter when NMs are incorporated into electrospun PS, the type, and morphological properties of the NMs played a critical role on their application potential as an adsorbent for water treatment. Further advances in fiber synthesis are needed such as higher NM loadings in fibers, partial exposure without compromising the composite integrity and continuous pores that allow pollutant access to NM surfaces where adsorption occurs.